Acute effect of different velocity-based training protocols on 2000-meter rowing ergometer performance - Quidel-Catrilelbún, M. E. L.; Ruiz-Alias, S. A.; García-Pinillos, F.; Ramirez-Campillo, R.; Pérez-Castilla, A. (The Journal of Strength and Conditioning Research, 2024)
This study aimed to explore the acute effect of 4 velocity-based resistance training (VBT) protocols on 2000-m rowing ergometer (RE2000) time trial, as well as the behavior of the maximal neuromuscular capacities when RE2000 is performed alone or preceded by VBT protocols in the same session. Fifteen male competitive rowers (15-22 years) undertook 5 randomized protocols in separate occasions: (a) RE2000 alone (control condition); (b) VBT against 60% of 1 repetition maximum (1RM) with a velocity loss in the set of 10% followed by RE2000 (VBT60-10 + RE2000); (c) VBT against 60% 1RM with a velocity loss in the set of 30% followed by RE2000 (VBT60-30 + RE2000); (d) VBT against 80% 1RM with a velocity loss in the set of 10% followed by RE2000 (VBT80-10 + RE2000); (e) VBT against 80% 1RM with a velocity loss in the set of 30% followed by RE2000 (VBT80-30 + RE2000). The load-velocity relationship (load-axis intercept [L0], velocity-axis intercept [v0], and area under the load-velocity relationship line [Aline]) was used to evaluate the maximal neuromuscular capacities during the prone bench pull exercise before and after each protocol. The time trial was significantly longer for VBT60-30 + RE2000 and VBT80-30 + RE2000 than for RE2000, VBT60-10 + RE2000 and VBT80-10 + RE2000 (all p < 0.001; ES = 0.10-0.15). L0 and Aline were significantly reduced after all protocols (p < 0.001; ES = 0.10-0.13), with Aline reduction more accentuated for VBT60-10 + RE2000, VBT60-30 + RE2000, VBT80-30 + RE2000, and RE2000 (all p = 0.001; ES = 0.11-0.18) than for VBT80-10 + RE2000 (p = 0.065; ES = 0.05). Therefore, VBT protocols with greater velocity loss in the set (30% vs. 10%) negatively affected subsequent rowing ergometer performance, in line with impairment in Aline pulling performance.